MODEL PENDIDIKAN NON FORMAL LEMBAGA BIMBINGAN BELAJAR MENTARI ILMU 3 KECAMATAN SUKUN KOTA MALANG - Romadhon, Beril Firmansyah (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
Formal education is a systematic, structured, complex, and tired, started from elementary school until higher education. Informal education is a long life process. Because of its characteristics, this type of education is able to give a strong influence on individual personality development. Meanwhile, non-formal education is all kinds of education that are conducted deliberately, orderly, and planned. It is separated from formal education since it aims to educate certain students in achieving the learning objectives. This study aims to: (1) identify the non-formal education model of Mentari Ilmu 3 learning course institution in Sukun, Malang, (2) find out the result of the non-formal education program evaluation in Mentari Ilmu 3 learning course institution in Sukun, Malang, and (3) know the factors that inhibit and support the implementation process of Mentari Ilmu 3 learning course institution in Sukun, Malang. This study uses a qualitative method as a part of the procedure of the study producing descriptive-qualitative data in written and spoken form. The data are obtained from the people and attitudes observed. The data collection techniques are observation, interview, and documentation. The results of the study are: (1) the education model of the Mentari Ilmu 3 learning course institution in Sukun, Malang is non-formal education, in which the curriculum is made based on the K13 curriculum. (2) The results of the non-formal education program evaluation conducted in Mentari Ilmu 3 learning course institution in Sukun, Malang consists of general evaluation held by LAZIZMU and special evaluation held by the internal party of the learning course institution, (3) the factors inhibiting the implementation process of Mentari Ilmu 3 learning course institution program in Sukun, Malang are the untidy management system, minimum coordination and commitment from the tutor, unclear target, and a minimum number of educators.Keywords: education model; non-formal; learning course institution